CINEMATOGRAPHY ANALYSIS OF THE ROMANTIC SCENE OF THE KOREAN DRAMA SERIAL EXTRAORDINARY ATTORNEY WOO - Nugraeni, Elara Karla; Sadewa, Ghalif Putra (Acintya, 2024)
Korean serial drama Extraordinary Attorney Woo achieved high popularity following its release on Netflix mid-year 2022. This drama does not only present relevant social issues but also offers captivating visual arrangements depicting emotions for the main character, who has asperger syndrome or autism. This study focuses on cinematographic patterns in romanticizing scenes to project thoughts and emotional expressions of the main character. From the total sixteen episodes, several scenes were selected through purposive sampling to demonstrate repetitive cinematic structures. Analysis was conducted using David Bordwell and Kristin Thompson’s developed theory of cinematography, encompassing three primary aspects: The Photographic Images, Framing and Duration of the Image. The aim of this study is to identify the visual patterns used in romanticizing those scenes, and how these visual arrangements build emotional engagement and deep understanding between viewers and Woo Young Woo as an individual with autism. This study is expected to enrich insights about visual construction within serials and films, particularly in potraying autistic characters through cinematography.